2018
DOI: 10.1002/ep.13009
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption characteristics of methyl blue onto magnetic Mn0.5Co0.5Fe2O4 nanoparticles prepared via a rapid combustion process

Abstract: A rapid combustion process for the preparation of magnetic Mn0.5Co0.5Fe2O4 nanoparticles was introduced, which was composed of the preparation process of solution, combustion process and calcination process. The structure and properties of the as‐prepared product were investigated by X‐ray diffraction, scanning electron microscopy, transmission electron microscopy, and vibrating sample magnetometer. The results revealed that the volume of absolute alcohol and the calcination temperature were two key parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…[59 The Freundlich model is an empirical equation that assumes the heterogeneous surface of the adsorbent, on which the adsorbed molecules are interactive. [53] The linear form of the Freundlich isotherm is expressed as Equation ( 11) by plotting log C e versus log q e [58] : where K F and n are the Freundlich adsorption isotherm constants. Both can be determined from the intercept and the slope of the linear plot, and indicate the extent of the adsorption and the degree of nonlinearity between the dye solution concentration and the adsorption respectively.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
See 1 more Smart Citation
“…[59 The Freundlich model is an empirical equation that assumes the heterogeneous surface of the adsorbent, on which the adsorbed molecules are interactive. [53] The linear form of the Freundlich isotherm is expressed as Equation ( 11) by plotting log C e versus log q e [58] : where K F and n are the Freundlich adsorption isotherm constants. Both can be determined from the intercept and the slope of the linear plot, and indicate the extent of the adsorption and the degree of nonlinearity between the dye solution concentration and the adsorption respectively.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…where K J (L g À1 ) is the parameter of the Javanovic model. [52] Ni 0.5 Zn 0.5 Fe 2 O 4 NPs Methyl Blue 54.70 Liu et al [53] Polyethersulfone/GO Methyl Blue 62.50 Zhang et al [54] XGCF [55] Bottom ash Basic Fuchsine 6.40 Gupta et al [55] CoVP Basic Fuchsine 32.63 Nistor et al [56] XGCF The graphic representation of the isotherm models is shown in Figures S6 and S7. For the Freundlich, Temkin, and Javanovic isotherms models, R 2 presents low values and the specific determined parameters (k F , k T , and q max J ) do not correlate with the experimental data.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…The Langmuir model assumes that the adsorption of the adsorbate on the adsorbent is a monolayer, its adsorption capacity depends on the occupation rate of the active sites on the adsorbent surface, and the interface energy is uniform [29]. However, the Freundlich model assumes that the adsorption of adsorbate on the adsorbent is heterogeneous, the active sites are first occupied, and then the binding energy decreases with an increase in the number of occupied sites [10]. Whereas the Temkin model considers the adsorbent and the q e and q t were the qualities of adsorbed RR-2BF at equilibrium and a sampling time (mg•g −1 ), respectively [10]; k 1 (min −1 ), k 2 (g•mg −1 •min −1 ), and k i (mg•g −1 •min −1 ) were the rate constants [29]; and x i was associated to the thickness of the boundary layer.…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…However, the Freundlich model assumes that the adsorption of adsorbate on the adsorbent is heterogeneous, the active sites are first occupied, and then the binding energy decreases with an increase in the number of occupied sites [10]. Whereas the Temkin model considers the adsorbent and the q e and q t were the qualities of adsorbed RR-2BF at equilibrium and a sampling time (mg•g −1 ), respectively [10]; k 1 (min −1 ), k 2 (g•mg −1 •min −1 ), and k i (mg•g −1 •min −1 ) were the rate constants [29]; and x i was associated to the thickness of the boundary layer. adsorbate to interact, and the adsorption heat linearly decreases with an increase in the coverage [31], the binding energy is uniformly distributed, and it increases to a maximum binding energy.…”
Section: Adsorption Isothermmentioning
confidence: 99%
See 1 more Smart Citation